Dynamic characteristics of electromechanical coupling of wind turbine drive system under multi‐source excitation. Issue 3 (30th September 2021) - Chen, Ruibo; Qin, Datong; Yi, Yuanyuan; Liu, Changzhao; Shi, Junren
Abstract: With the rapid development of wind turbine, the operational reliability of the main drive systems of wind turbine has received extensive attention. The wind turbine drive system is affected not only by random wind loads for a long time but also by the electromagnetic torque of the generator. Exploring the coupling behavior and mechanism is particularly important for optimizing the design of the drive system and improving the operational reliability of the main drive system. This study establishes a mechanical–electrical coupling model, which includes a translational–torsional dynamic model of a gear transmission system that can be used for variable speed and variable‐load conditions, a finite element model of the generator, and voltage vector control. This model takes into account nonlinear factors such as the time‐varying meshing stiffness of the gear system and the magnetic characteristics of the generator. The speed sweep analysis method was used to identify the resonance speed and dangerous components of the system. Under different external excitation conditions, the dynamic characteristics of the system were compared with and without considering electromagnetic characteristics. The generator speed of 1030 r/min and 651 r/min is the potential resonance speed of the system. The gear system and generator system have strong coupling characteristics. In the vibration signal of the gear system, there will be electrical system frequency components dominated by 6 kf e and ( h − 1) f e . In the current signal, not only appeared the excitation frequency in the gear system, but also the modulation signal with the excitation frequency in the gear system as the carrier frequency and the electric frequency as the fundamental frequency ((6 k ± 1) ⋅ f e ± n ⋅ f m ) appeared. Under the gust wind, the transient response of the system will excite the gear‐generator coupling vibration mode. The electromagnetic characteristic of generator can suppress the vibration of mechanical system.